CONDITIONS AND CHARACTERISTICS OF THE RULER AND MODELS OF HIS ADMINISTRATION IN THE HOLY QUR’AN - Awad Khalifah, Husam (International Journal of Advance Research in Education & Literature (ISSN 2208-2441), 2024)
Praise be to Allah, Lord of the Worlds, and prayers and peace be upon our Master Muhammad and his family and companions, As for after.In my research, I spoke about the most important lines regarding the ruler and his system of rule, because governance is a trust, and this trust will be asked about by all the ruler on the Day of Resurrection. Was it used for good and righteousness or vice versa? The ruler derives authority from the nation by virtue of the people’s sale to him, i.e. (elections). Among his duties is not His constitution must be just, derived from the Qur’an and the Sunnah. Likewise, the ruler has many duties, the most important of which is the moral, religious, economic, and political goal in a way that guarantees the interests of the people. Islamic civilizations have witnessed many great rulers whose work was crowned by the true faith that made the limbs work and the hearts trust in the service of the subjects. Many Of rulings, they were characterized by this, and they took practical and scientific reasons, based on their example, our master Muhammad, peace be upon him. In my research, I emphasized the most important qualities and conditions for that ruler and the method of choosing those who participate in governance with him from among the ministers, workers, and scholars who pretend to be all kinds of honesty, professionalism, and good management in religion and justice. And staying away from injustice, all of which is derived from the Qur’an and the Sunnah of the Prophet. Likewise, in my research, I touched on Allah’s ability to remove the ruler. Likewise, I wrote many deductions and results that serve the ruler and balance between his work and his subjects in a way that serves the servants.